(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides information about the life and scientific work of Abu Rayhan Beruni, one of the great encyclopedists of his time. Information is provided about the creation of Abu Rayhan Beruni’s works and their study.